Comparing colorectal cancer treatment and survival for Aboriginal and non‐Aboriginal people in New South Wales. Issue 4 (7th March 2016) - Weir, Kristie; Supramaniam, Rajah; Gibberd, Alison; Dillon, Anthony; Armstrong, Bruce K; O'Connell, Dianne L
Abstract: Objectives: Our aim was to compare surgical treatment rates and survival rates for Aboriginal and non‐Aboriginal people in New South Wales with colorectal cancer, and to describe the medical treatment received by a sample of Aboriginal people with colorectal cancer. Design, setting and participants: All people diagnosed with colorectal cancer in NSW during 2001–2007 were identified and their cancer registry records linked to hospital admissions data and death records. A medical records audit of a sample of Aboriginal people diagnosed with colorectal cancer during 2000–2011 was also conducted. Main outcome measures: Cause‐specific survival, odds of surgical treatment, and the proportions of people receiving adjuvant treatments. Results: Of 29 777 eligible colorectal cancer cases, 278 (0.9%) involved Aboriginal people. Similar proportions of Aboriginal (76%) and non‐Aboriginal (79%) people had undergone surgical treatment. Colorectal cancer‐specific survival was similar for Aboriginal and non‐Aboriginal people up to 18 months after diagnosis, but 5 years post‐diagnosis the risk of death for Aboriginal people who had had surgical treatment was 68% higher than for non‐Aboriginal people (adjusted hazards ratio, 1.68; 95% CI, 1.32–2.09). Of 145 Aboriginal people with colorectal cancer identified by the medical records audit, 117 (81%) had undergone surgery, and 56 (48%) had also received adjuvant chemotherapy and/or radiotherapy. Conclusions: Aboriginal people with colorectal cancer had poorer survival rates than non‐Aboriginal people, although rates of surgical treatment, complications and follow‐up colonoscopy were similar. More work is needed to identify and understand why outcomes for Aboriginal people with colorectal cancer are different from those of other New South Wales residents.